Macrozoobenthos in an altitudinal gradient in North Patagonian Cautín River (Araucanía Region, Chile) - Figueroa,D. (2022)
Abstract The Cautín River is closely related with the economic development of Temuco city, (38°S; Chile). Existing knowledge of the Cautín River is limited to information about its biological characteristics as a reference for the evaluation and assessment of water quality. The object of this study was to develop taxonomic characterisation of the benthic macroinvertebrates along the main course of the Cautín River, and to study the community structure using correlation analysis between community parameters. To carry out this research, the macroinvertebrate community was studied in 10 sampling sites distributed along the main course of the river. The samples were taken in summer (1997 and 2000), when optimal hydrological conditions existed. Analysis of the samples showed that the benthic fauna was composed of 56 taxa, the dominant group being insects with 48 taxa. Three main sectors were recognised in the course of the Cautín River: high, middle and low. Each sector has restricted-distribution species, while other species are widely distributed along the river. These distribution patterns seem to be influenced by dissolved oxygen concentration, temperature, altitudinal distribution and anthropo-cultural activity, present at every sampling site. Finally, this research provides a first approach to the biology of the Cautín River. Further studies could be planned on the basis of this knowledge to investigate water quality indicators based on macroinvertebrate communities.